Cecal microbiome profile altered by Salmonella enterica, serovar Enteritidis inoculation in chicken - Liu, Liying (Gut Pathog, 2018)
BACKGROUND: Salmonella enterica, serovar Enteritidis (S. Enteritidis), an important zoonotic foodborne pathogen, can affect the microbiota of the chicken intestine and cause many enteric diseases, such as acute gastroenteritis. The gut microbiota contributes to the development and function of the host immune system and competes with pathogenic microbes. The interaction between S. Enteritidis and the host cecal microbiota is still not fully understood. We investigated the microbiome composition in both treated and control groups through 16S ribosomal RNA (rRNA) gene sequencing at 1, 3, 7, 14, 21, 28, and 35 days post-S. Enteritidis inoculation (dpi) in the current study. RESULTS: Chao1 richness and Shannon diversity significantly increased with chicken development in both the treated and control groups (P < 0.05). The Chao1 index was significantly lower in the treated group than that in the control group at 14 dpi (P < 0.05). Phyla Proteobacteria and Firmicutes were most dominant at 1 and 3 dpi. S. Enteritidis inoculation influenced cecal microbiota mainly at 7 and 14 dpi. S. Enteritidis inoculation significantly altered the relative abundance of 18 genera at different time points (P < 0.05) with relative abundance significantly changed after 14 dpi. The abundance of those genera changed dramatically between 28 and 35 dpi in the treated group compared to control group. Positive correlations existed between Bacillus and Blautia and between Coprococcus and Flavonifractor following S. Enteritidis inoculation. CONCLUSIONS: Our results indicated that both development and S. Enteritidis have effect on chicken cecal microbiota profiles. S. Enteritidis inoculation in young chicks influences the cecal microbiota mainly at 7 and 14 dpi. The cecal microbiota exhibited immunity to S. Enteritidis inoculation at 28 dpi. These findings will provide basic knowledge of the role that chicken cecal microbiota play in response to S. Enteritidis inoculation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13099-018-0261-x) contains supplementary material, which is available to authorized users.